Dietary Probiotic Supplementation on Hematological and Immunological Parameters of Indian Major Carp (Labeo rohita) - Priyadharshini, J.; Margaret, I. Viji; Nisha, M. Barakath; Mohideen , R. Ajaz Haja (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
A 60-day feeding trial was conducted to evaluate the influence of dietary supplementation of probiotic bacteria (Lactobacillus acidophilus) to improve the hematological and immunological parameters of Indian Major carp Rohu (Labeo rohita). The rohu Fingerlings (mean body weight 6.0±0.6g) were randomly distributed into Four treatment groups each having 10 fishes fed with basal diet and a probiotic supplement containing L. acidophilus (1.0×107 CFU/g), then challenged with A. hydrophila (0.1 × 107 CFU/mL) was injected intraperitoneally with 0.1ml concentration of 107 CFU/ml on 55th day. After 72 hours, the blood samples were collected from five fish from each group. The hematological parameters such as hemoglobin (Hb; g/dL), red blood cell (RBC; ×106/mm3), white blood cell (WBC; ×103/mm3), and Packed corpuscular volume (PCV) along with immunological parameters of total immunoglobulin, serum lysozyme activity, and Aminotransferases were examined and compared with the control group. The fish fed with probiotics showed significant improvement in hematological and Immunological Parameters (P≤0.05) as compared to control. This study proved that probiotic bacteria L. acidophilus are resistant to pathogenic A. hydrophila and can contribute to improving the immune system, survival rate, and growth of experimental fish against the fish pathogen A. hydrophila.